The impact of the initial Covid-19 lockdown upon regular sports bettors in Britain: Findings from a cross-sectional online study. (July 2021) - Wardle, Heather; Donnachie, Craig; Critchlow, Nathan; Brown, Ashley; Bunn, Christopher; Dobbie, Fiona; Gray, Cindy; Mitchell, Danielle; Purves, Richard; Reith, Gerda; Stead, Martine; Hunt, Kate
Highlights: Analysis of regular sports bettors' behaviour change during the first Covid-19 lockdown. For most, reducing or stopping gambling during the initial lockdown was the norm. Problem gambling was associated with starting new gambling activities during lockdown for men. Women shielding for health reasons were more likely to experience gambling harms. Low wellbeing also associated with harms. Cross-selling of products by industry during lockdowns should be discouraged. Abstract: Background: In Britain, unprecedented restrictions on daily life associated with the Covid-19 pandemic included the suspension of professional sports events during the initial 'lockdown'. This provides opportunities to observe changes in sports bettors' behaviour when their primary form of activity is removed and assess the impact of Covid-19 related circumstances upon gambling. Methods: In July 2020, we conducted an online cross-sectional survey of people who bet regularly (at least monthly) on sports before Covid-19 (n = 3866). Bi-variate analyses compared changes in gambling behaviours before and during the initial lockdown. Multi-variate logistic regression models explored associations between problem gambling (men) and moderate risk or problem gambling (MRPG) (women) with changes in Covid-19 related circumstances and changing gambling behaviours during Britain's initial 'lockdown' (March-June 2020). Results: 29.8% of male sports bettors and 33.4% of female sports bettors stopped gambling altogether during the initial Covid-19 lockdown, though 17.3% of men and 16.5% of women started a new form of gambling during lockdown. Among men, adjusted odds ratios of problem gambling were higher among those starting a new gambling activity during lockdown (OR = 2.50 [95% CI 1.38–4.53]). Among women, adjusted odds ratios of MRPG were higher among those whose frequency of gambling on any activity increased during lockdown (OR = 4.21 [1.99–8.92] and among those shielding for health reasons. Poorer wellbeing was associated with problem gambling for men and MRPG for women. Conclusions: Those changing gambling behaviours during the initial Covid-19 lockdown (e.g. increasing gambling frequency or starting a new gambling activity) are potentially vulnerable to gambling harms.